Pengaruh Kualitas Produk, Kualitas Pelayanan, Harga Dan Promosi Terhadap Keputusan Pembelian Knalpot Home Industry - Fajar Hamid Alwi; Ahsan Sumantika; Anindita Imam Basri; Kasnowo Kasnowo (CV. Aksara Global Akademia, 2024)
The development and the increasing number of business actors engaged in the industrial sector has resulted in competition in business becoming increasingly sharp and competitive, both in terms of quality, price and the way promotions are carried out. The purpose of this study was to determine the effect of product quality, service quality, price and promotion on purchasing decisions for FEZ Racing Exhaust brand exhaust. The method used is a quantitative method. The population in this study were consumers who purchased FEZ Racing. The sample used was 80 respondents who were selected using a convenience sampling technique. Data analysis used using multiple linear regression analysis. The results of the study prove that simultaneously product quality, service quality, price, promotion influence purchasing decisions. In partial variable testing for the variable product quality, service quality, price, promotion proves that there is a positive and significant influence on the purchase of FEZ Racing Exhaust brand exhaust.